Literacy disparities in patient access and health‐related use of Internet and mobile technologies. (2nd November 2014) - Bailey, Stacy C.; O'Conor, Rachel; Bojarski, Elizabeth A.; Mullen, Rebecca; Patzer, Rachel E.; Vicencio, Daniel; Jacobson, Kara L.; Parker, Ruth M.; Wolf, Michael S.
Abstract: Background: Age and race‐related disparities in technology use have been well documented, but less is known about how health literacy influences technology access and use. Objective: To assess the association between patients' literacy skills and mobile phone ownership, use of text messaging, Internet access, and use of the Internet for health‐related purposes. Methods: A secondary analysis utilizing data from 1077 primary care patients enrolled in two, multisite studies from 2011–2013. Patients were administered an in‐person, structured interview. Results: Patients with adequate health literacy were more likely to own a mobile phone or smartphone in comparison with patients having marginal or low literacy (mobile phone ownership: 96.8 vs. 95.2 vs. 90.1%, respectively, P  <   0.001; smartphone ownership: 70.6 vs. 62.5 vs. 40.1%, P  <   0.001) and to report text messaging (78.6 vs. 75.2 vs. 53.1%, P  <   0.001). They were also more likely to have access to the Internet from their home (92.1 vs. 74.7 vs. 44.9%, P  <   0.001) and to report using the Internet for email (93.0 vs. 75.7 vs. 38.5%, P  <   0.001), browsing the web (93.9 vs. 80.2 vs. 44.5%, P  <   0.001), accessing health information (86.3 vs. 75.5 vs. 40.8%, P  <   0.001), and communicating with providers (54.2 vs. 29.8 vs. 13.0%, P  <   0.001). Relationships remained significant in multivariable analyses controlling for relevant covariates. Conclusions: Results reveal that literacy‐related disparities in technology access and use are widespread, with lower literate patients being less likely to own smartphones or to access and use the Internet, particularly for health reasons. Future interventions should consider these disparities and ensure that health promotion activities do not further exacerbate disparities.